Budaya organisasi sebagai pemoderasi pengaruh antara asimetri informasi, ketaatan aturan akuntansi, dan kesesuaian kompensasi terhadap kecenderungan kecurangan akuntansi (Studi empiris pada OPD Kabupaten Indragiri Hulu) - Alfiati Silfi; Nita Wahyuni (Pelantar Press, 2021)
This study aims to examaine the effect of Organizational Culture as moderated variable for influencing the relationship among Asymetri Information, Complience with Accounting Rules, the Suitability Compensation toward accounting fraud.The sample used in this study is there are agencies in Indargiri Hulu. Collecting data through a questionnaire survey method.The data analysis used multiple regression analysis with SPSS. The result showed that Asymetri Information has significant effect to Accounting Fraud. But the othervariables like compliance with accounting rules, suitable compensation did not influence the accounting fraud. The moderated analysis shows that there was no significant effect of Organization Culture to moderate the relationship between Asymetri Information, Complience with Accounting rules, Suitable Compensation toward Accounting Fraud.